Estimating Economic Efficiency in Paddy Farms: A Case of Northwest Selangor IADP - Radam, Alias; Latiff, Ismail (Universiti Putra Malaysia Press, 1996)
Economic efficiency can be measured as allocative and technical efficiency. A study to measure the technical, allocative and economic efficiency of paddy farms using the probabilistic frontier production function was carried out. Results showed that the sample paddy farmers under study are economically inefficient. There is still in technical efficiency a 15 percent potential for in creasing the output of farmers, and a 35 percent potential in allocative efficiency to increase output optimally. The government should therefore play a part in directing education, extension, and social change and provide institutional support in order to improve the farmers' efficiency technically and allocatively.